(3GdcGed aj eYQaI VYaGA GdeMOKjf hYdd GdCMGOjKs - (3GHf YOj , YHO Gddg Hf YOj Hf YHO Gddg Hf eMeO Hf GdeHGQc GdLQLGfj, CHh CMeO,J (B365 (3g` s
(3ChdgG (B:s
(3Chd eG ajg GSe (B: (3eYdi Hf gdGd s
(3BNQgG (B:s
(3hjfJgi HBNQ GdcJGH s
(3hYdi GdhQbI GdChdi hQO Cfg efJNH ef GdcGed dGHf YOis
(3hHBNQg NW GdMGaX VjGA GdOjf GdebOSi HbQGAI GdeLdO Ydi TjNg YHO GdhGMO Hf YHO GdSdGe Hf GdSdWGf GdHjY ai SfI (B601(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B82s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs